Vitamin D and atopy and asthma phenotypes in children: A longitudinal cohort study - Hollams, E.; Hart, P.; Holt, B.; Serralha, M.; Parsons, F.; De Klerk, N.; Zhang, Guicheng; Sly, P.; Holt, P. (2011)
Vitamin D has been linked in some studies with atopy- and asthma-associated phenotypes in children with established disease, but its role in disease inception at the community level is less clear. The aim of the present study was to investigate associations between vitamin D status and biological signatures indicative of allergy and asthma development in children aged 6 and 14 years in Perth, WA, Australia (latitude 32° S). Serum vitamin D was assayed in 989 6-yr-olds and 1,380 14-yr-olds from an unselected community birth cohort; 689 subjects were assessed at both ages. Vitamin D levels were assessed as a risk modifier for respiratory and allergic outcomes at both ages, using previously ascertained phenotypic data. The predictive value of vitamin D levels at age 6 yrs for development of clinical phenotypes at age 14 yrs was also examined. Serum vitamin D levels in children of both ages were negatively associated with concurrent allergic phenotypes; sex stratification revealed that this association was restricted mainly to males. Furthermore, vitamin D levels at age 6 yrs were significant predictors of subsequent atopy/asthma-associated phenotypes at age 14 yrs. In an unselected community setting, children (particularly males) with inadequate vitamin D are at increased risk of developing atopy, and subsequently bronchial hyperresponsiveness (BHR) and asthma. In a large unselected cohort, males with inadequate vitamin D at 6 and 14 yrs of age had increased atopy and BHR. Low vitamin D at age 6 yrs was a predictor of atopy and asthma at 14 yrs of age. Copyright©ERS 2011.